Aquaculture in Egypt: Insights on the Current Trends and Future Perspectives for Sustainable Development. Issue 1 (2nd January 2018) - Shaalan, Mohamed; El-Mahdy, Magdy; Saleh, Mona; El-Matbouli, Mansour
ABSTRACT: Aquaculture has been practiced in Egypt for millennia, but modern approaches have only recently been adopted to maximize its output. Today, aquaculture production in Egypt is the largest in Africa with about one million tonnes per annum. In this review, different freshwater and marine fish species that are cultured in Egypt are reviewed; the most important species are the tilapias, followed by mullets and carps. Current practices for aquaculture in Egypt are highlighted, which include extensive, semi-intensive and intensive aquaculture systems, integrated aquaculture systems, aquaponics and rice-field aquaculture, desert aquaculture and mariculture. This review focuses on the constraints that threaten fast growing and sustainable development of aquaculture industry, such as production costs, availability of feed and seed, lack of current technologies for feed production and domestic regulations. Also, the future perspectives with regard to overcoming of these obstacles are presented.